Managerial simulators as significant learning tools (2015)
Managerial simulators promote an active learning in several scenarios that recreate real situations where business areas as management, finance, human resources and marketing are involved. In addition, strategic decisions are integrated as an important basis for decision making .With these simulators, individuals are in a constant process of learning and practice in a dynamic context, developing entrepreneurial skills learned.